ZONASI WILAYAH RAWAN BANJIR SUB DAS WAY KANDIS HULU DENGAN PENDEKATAN GEOSPASIAL - Sekar Dwi Rizki; Didik Kuswadi; Muhammad Idrus; Adi Purnomo (Departement of Civil Engineering, Universitas Winaya Mukti, 2026)
The land used in Bandar Lampung City has changed significantly. Bandar Lampung City has experienced flooding issues for the last five years. In order to anticipate and lessen the effects of flood disasters, maps identifying locations that was prone to flooding were created as an early warning system. This study aims to map the degree of flood risk in the Way Kandis Hulu Sub-watershed area and zoning areas according to flood vulnerability. The geospatial method used to create this map includes the division of flood vulnerability class intervals, flood vulnerability level zoning analysis, meteorological thematic maps, flood variables that were scored and weighted, an overlay process, and watershed features that contribute to flooding. The Way Kandis Hulu Sub-watershed's level of flood susceptibility was classified as low, medium, and high based on the analysis, which showed that the value interval for the flood vulnerability class reached 150. According to the analysis, Rajabasa District received the highest score for flood vulnerability, covering an area of 3.2153 km2, or 41.30% of the Way Kandis Hulu Sub-DAS's total area. The high Risc zone has the highest level of flood vulnerability, with an area of 7.7585 km2 (99.66%).